Fatores indicativos de alterações climáticas associados à exploração petrolífera onshore na Bacia Potiguar - Alves, Agassiel de Medeiros (2018)
The Potiguar Basin, located on the northern coast of Rio Grande do Norte, is a region with great potential for energy exploration. It is currently the largest onshore oil exploitation area in Brazil. Associated with this are other forms of active renewable energies, such as biomass and wind energy, which are also explored in the study area. The present work deals with the onshore oil exploration that occurs in the Potiguar Basin, under the focus of changes in the albedo index and surface temperature associated with climate change. The albedo is considered a significant variable in the understanding of the energy balance of the terrestrial surface, since it is a biophysical parameter of surface, which composes element of the analysis of global climatic changes. The surface temperature is directly related to the conditions of preservation of the natural characteristics of the area where it is evaluated in relation to the type of use and occupation used in it. Through the use of remote sensing tools and Geographic Information System (GIS) using the scenes produced by the Landsat-8 satellite, it was possible to determine albedo index and surface temperature variations in the oil fields in the Potiguar Basin using the 6S methods, the one proposed by LIANG and the GEOBia. The influence of these forms of exploration in the areas of conservation units in the study area, the Sustainable Development Reserve of Ponta do Tubarão and the Assú National Forest were also analyzed. In view of the obtained data, it can be verified that, although it is the largest area of oil exploitation onshore in the country, they have lower rates of climate change than other areas of energy exploration considered renewable due to geosystemic changes. Surface albedo values related to oil exploitation are concentrated in the range of 0.1890 to 0.1929. There are areas with high natural potential of albedo reflectance, located in dune fields, outcrops of sandstones and limestone, and clear soils. The variations of surface temperature, another important climatic variable, stand out with higher rates of change, in areas associated with energy exploration, even if it is one of the regions with the highest temperature indices in the country, reaching a maximum of 37,20ºC to 41 , 76ºC well above the average of 32,30ºC, mainly in the central area of the Potiguar Basin associated specifically to the exploitation of biomass.